Experience of a new high‐purity factor X concentrate in subjects with hereditary factor X deficiency undergoing surgery. (24th May 2016) - Escobar, M. A.; Auerswald, G.; Austin, S.; Huang, J. N.; Norton, M.; Millar, C. M.
Abstract : Introduction: Maintaining haemostasis in surgery is challenging for hereditary rare bleeding disorders in which multi‐coagulation‐factor concentrates are the only therapeutic option. Hereditary factor X (FX) deficiency affects 1:500 000 to 1:1 000 000 individuals, and no specific replacement FX concentrate has been available. A high‐purity, plasma‐derived FX concentrate (pdFX) has been developed for patients with hereditary FX deficiency. Aim: Our objective was to assess the safety and efficacy of pdFX in subjects with FX deficiency undergoing surgery. Methods: Subjects with hereditary mild‐to‐severe FX deficiency (basal plasma FX activity [FX:C] <20 IU dL −1 ) undergoing surgery received pdFX preoperatively to raise FX:C to 70–90 IU dL −1 and postoperatively to maintain levels >50 IU dL −1 until the subject was no longer at risk of bleeding due to surgery. Efficacy of pdFX was assessed by blood loss during surgery, requirement for blood transfusion, postoperative bleeding from the surgical or other sites, and changes in haemoglobin levels. Safety was assessed by adverse events (AEs), development of inhibitors, and clinically significant changes in laboratory parameters. Results: Five subjects (aged 14–59 years) underwent seven surgical procedures (four major and three minor). Treatment duration was 1–15 days. For each procedure, pdFX treatment was assessed as "excellent" in preventing bleeding and achieving haemostasis. No blood transfusions were required, no AEs related to pdFX were observed, and no clinically significant trends were found in any laboratory parameters. Conclusion: These data demonstrate that pdFX is safe and effective as replacement therapy in five subjects with mild‐to‐severe FX deficiency undergoing surgery on seven occasions.